Analyzes of efficiency in practical training with use of construction machin er simulators - Rychlik, Kazimierz; Araszkiewicz, Stanisław (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2018)
The paper presents an analysis of effectiveness in practical training and progress in acquiring practical skills using simulation techniques using the simulator of the Volvo ECX21 O one-bucket excavator. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)